Pembatalan Merek PT. Sumatra Tobacco Trading Company Akibat Persamaan Pada Pokoknya Dengan Merek Dagang Starbuck Corporation - Matakena, Anjelin Jei; Haliwela, Nancy Silvana; Pariela, Marselo Valentino Geovani (Faculty of Law Universitas Pattimura, 2024)
In the world of trade, related to a brand used on a product, as regulated in Act Number 20 of 2016, concerning Brand and Geographical Indications. Brands are a form of intellectual work that play an important role in the effectiveness and improvement of trade in goods and services. Brands are also a differentiating factor, with each good and service having their own personalized apperance, so that consumers can easily recognize a good or service. However, legal regulations in the field of brands and geographical indications do not fully support the registration of trademarks in Indonesia, which caused similarities between brands. This can be seen in the brand cancellation issue between Starbucks Corporation and PT Sumatra Tobacco Company (STTC) which was caused by trademark similarities. The legal research method used for this research is based on primary, secondary and tertiary legal materials, and uses a statutory approach and a conceptual approach. The results of the research show that the brand registration between Starbucks Corporation and PT.Sumatra Tobacco Company (STTC) experienced trademark similarities, which essentially resulted in a brand cancellation. The legal consequences of a brand cancellation that occur consists of PT. Sumatra Tobacco Company (STTC) to no longer use the